Effectiveness of RADEC Learning Model in Developing Critical Thinking Skills of Elementary School Students: A Systematic Literature Review - Aji Purwanto; Wanda Nugraha Yanuarto (UM Purwokerto Press, 2025)
Background from this research is the increasing emphasis on critical thinking skills development in elementary education, particularly through innovative learning models like RADEC (Read, Answer, Discuss, Explain, and Create). This study aims to systematically analyze research findings on the effectiveness of the RADEC learning model in developing elementary school students' critical thinking skills. This research employed a systematic literature review method following the PRISMA protocol. Data were collected from 25 studies published between 2019-2025 meeting the inclusion criteria, sourced from reputable databases. The analysis revealed that the RADEC model significantly enhances elementary students' critical thinking skills, with average improvements ranging from 25.4% to 38.7% across various subjects. The pre-learning questions phase and discussion activities were identified as the most critical elements fostering critical thinking development. Implementation challenges included teacher preparation time, adaptation to student reading levels, and the need for continuous assessment strategies. This review concludes that the RADEC model offers a structured, effective approach to developing critical thinking in elementary education, particularly when implemented with appropriate scaffolding and contextual adaptations.